(untitled) (Research, Society and Development, 2023)
The consumption of mineral water began to be adopted by several families, as they presented standards of reliability, which over time made the high consumption index of these bottled waters grow massively. In this way, in the State of Pernambuco, it is no different, there are a large number of mineral water companies in deplorable conditions and which have been increasing the level of unreliability in the safety of these waters for human consumption. Thus, in recent years, there has been a significant growth in the irregularities of these waters. This fact is linked to the insertion in the market of a large number of companies that supply drinking water with added salts, which requires greater inspection by the inspection bodies. Therefore, the objective of this study is to evaluate the occurrence of Pseudomonas Aeruginosa in mineral water samples of different brands marketed in the metropolitan region of Recife, Pernambuco, using the multiple tube method, as recommended in the Standard Methods for the Examination of Water and Wastewater, through the Presence and Absence Tests (P-A). In this way, the main results indicate that between the periods (January to April) and (June to August) of the year 2015, for the seven brands of mineral water analyzed, two were compromised due to the presence of Pseudomonas Aeruginosas. There were no differences that could relate the periods studied with the presence of contaminants in the water. This points to the need for more effectiveness in controlling and inspecting the quality of mineral water sold in the state. It was observed in the study that some companies are not strictly following the portability standards determined by Resolution n°275/2005. Finally, greater inspection of mineral water reservoirs is necessary, from the process of removing them from the water source (quality test, bottling) to their arrival at the final consumer, bearing in mind that this water is intended for exclusively for human consumption.